2005
DOI: 10.3354/meps292251
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in abundance, respiration and lipid composition of Arctic under-ice amphipods

Abstract: The Arctic under-ice amphipods Apherusa glacialis, Onisimus glacialis, O. nanseni andGammarus wilkitzkii are autochthonous below the pack ice, i.e. they occur in this habitat during all seasons. In this study, seasonal dynamics in abundance were only evident in A. glacialis. Respiration rates did not differ significantly between summer and winter in any species, indicating that the under-ice habitat is a comparatively stable environment in terms of seasonal variations. The assessment of total lipids and fatty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
(45 reference statements)
4
27
2
Order By: Relevance
“…Although the specific mechanism of WE assimilation is not yet known for hyperiids, we suggest that similarly the ingested WE have to undergo a metabolic transformation before passing through the gut membrane of T. libellula. This is in contradiction with the hypothesis raised by Werner and Auel (2005) who suggested that carnivorous under-ice amphipods might assimilate directly non-modified WE from their prey. This is the first time that a seasonal survey on the fatty acid composition of the amphipod T. libellula has been conducted.…”
Section: Storage Differences Between Tag and We Lipid Classescontrasting
confidence: 97%
“…Although the specific mechanism of WE assimilation is not yet known for hyperiids, we suggest that similarly the ingested WE have to undergo a metabolic transformation before passing through the gut membrane of T. libellula. This is in contradiction with the hypothesis raised by Werner and Auel (2005) who suggested that carnivorous under-ice amphipods might assimilate directly non-modified WE from their prey. This is the first time that a seasonal survey on the fatty acid composition of the amphipod T. libellula has been conducted.…”
Section: Storage Differences Between Tag and We Lipid Classescontrasting
confidence: 97%
“…The differences in growth rate could be explained by different feeding strategies. Based on our fatty acid composition data, O. nanseni seems to be a predator on calanoid copepods in addition to necrophagous feeding (Arndt et al 2005a), while O. glacialis is more herbivorous and thus more affected by the seasonality in primary production; although Werner & Auel (2005) suggest the latter species switches to a Calanus diet in winter. O. litoralis is also herbivorous-omnivorous, but it has been shown to feed year-round .…”
Section: Life Cyclesmentioning
confidence: 89%
“…Thus, O. nanseni and O. litoralis have feeding strategies that allow them to grow continuously throughout the year, and complete their life cycles in 2 to 2.5 yr. Although O. glacialis also feeds on detritus and Calanus in winter (Arndt et al 2005a, Werner & Auel 2005, it is probably mostly a seasonal feeder on ice algae. It therefore needs to build up lipid reserves (30% of DW in October) for overwintering and can not afford continuous growth.…”
Section: Life Cyclesmentioning
confidence: 99%
“…Soler-Membrives et al (2011) found a very similar trend to ours in the trophodynamics of the pycnogonid Ammothella longipes, which appears to be carnivorous during spring and early summer, but prefers detritus when prey availability diminishes during winter. Opportunistic feeding has been reported in amphipods on several occasions (Werner and Auel 2005;NunezPons et al 2012), as well as in herbivorous species, such as some talitrids (Bessa et al 2014). Opportunistic feeding can be a key factor in the success of an invasive species (Maazouzi et al 2007;Cook et al 2009).…”
Section: Discussionmentioning
confidence: 99%